Cellular electron tomographic analysis of heterochromatin - Chan, Harvey Yin Seng (Nanyang Technological University, 2021)
Packaging of nucleosomes into heterochromatin is an intricate process as many factors are involved in silencing of the transcriptional machinery in specific regions of DNA. Chromatin structure in vivo is not fully understood, while in vitro research on chromatin compaction carried out for many decades has only provided a glimpse into this highly complex system. Architectural factors involved in maintaining heterochromatin domains were tagged with enhanced green fluorescent protein (eGFP) and ascorbate peroxidase 2 (APEX2) for correlating eGFP-fluorescence-based confocal microscopy with transmission electron microscopy based on APEX2-mediated contrast. Analysis of the large imaging datasets generated show that the majority of heterochromatin fibers tagged with eGFP-APEX2-H1.0 or eGFP-APEX2-HP1α have a width of 11 nm to 20 nm, and the ones tagged with eGFP-APEX2-macroH2A have a width of 21 nm to 30 nm. This sheds light on chromatin heterogeneity and the influence of specific architectural factors on chromatin structure in the cell.